Understanding the hydration of alkali-induced duck egg white gel at high temperature. (May 2021) - Fan, Hong; Ai, Minmin; Cao, Yuanyuan; Long, Jiaoli; Li, Shuchang; Jiang, Aimin
Abstract: In this paper, prepared alkali-induced egg white gel (EWG) was treated at different temperatures (100–121 °C) to explore the hydration mechanism under high temperatures (≥100 °C). The physicochemical, mechanical and rheological properties and intermolecular interactions of the EWG were investigated. Results showed that with increasing temperature the pH, free alkalinity and surface hydrophobicity of EWG increased initially but then decreased, together with gel hydration, and the browning intensity increased markedly. The mechanical properties, including hardness, puncture strength and springiness, rheological characteristics―determined via apparent viscosity and frequency sweep results―and water-holding capacity significantly decreased as temperature increased. Fourier-transform infrared (FTIR) spectroscopy revealed that the β-sheet contents decreased significantly, and the α-helical and β-turn contents improved markedly with increasing temperature. The protein fraction results showed that hydrogen bonds, hydrophobic interactions and disulphide bonds were destroyed in the heating process. This study provides deep insights into EWG destruction under high temperature and the relationship with intermolecular interactions, enabling control over EWG quality. Highlights: The alkali-induced egg white gel will be hydration under high-temperature heating. The egg white gel will be liquefaction after heating 20 min for 121 °C. β-sheet contents decreased and β-turn contents increased obviously after heating. Hydrogen bonds, hydrophobicity interactions and disulfide bonds were destroyed after heating. The hydration of egg white gel is related to the alteration of molecular forces.